MORPHOLOGICAL ATTRIBUTES OF ROOT SYSTEM OF MAIZE GENOTYPES CONTRASTING IN DROUGHT TOLERANCE DUE TO PHOSPHORUS STRESS - CANTÃO, FERNANDO RODRIGO DE OLIVEIRA; DURÃES, FREDERICO OZANAN MACHADO; OLIVEIRA, ANTÔNIO CARLOS DE; SOARES, ÂNGELA MARIA; MAGALHÃES, PAULO CÉSAR (International Journal of Maize & Sorghum, 2010)
This work was carried out with the objective of evaluating morphological attributes of root system and growth characteristics of root and plant canopy of inbred lines selected for drought tolerance from the Embrapa Maize and Sorghum breeding program. Two drought tolerant and two sensitive inbred lines were seeded in seedling beds with different phosphorus levels (4 and 20mg/dm3). The experiment was manually seeded, using 0.20m row spacing and plants 0.20m apart in the line. The experimental plots consisted of four 1.2m long rows with five plants per linear meter. A randomized complete blocks design with three replications was used. Two evaluations of root system morphology using the digital image analysis system WinRHIZO and also evaluations of roots and plant canopy were done at 14 and 21 days after seeding. Significant differences were observed for root morphological attributes and root and canopy growth. Drought tolerant inbred lines showed distinct root system than sensitive, by presenting larger root length, surface area, volume, and greater contribution of roots with diameter less than 0.5 mm to total root length, in plants grown under low phosphorus availability conditions.